Promoting Carbon Reduction in Universities Through Carbon Footprint Assessments: A Framework and Case Study of a University in Northeast China - Zhijian Xiao; Shijiu Ma; Dehua Kou; Yu Zhang; Jianmin Gao (Energies)
To respond to the challenge of global climate change, universities should engage in carbon footprint research to identify effective strategies for mitigating greenhouse gas emissions. In this research, a comprehensive framework tailored for the study of carbon footprints in universities was constructed and used in a university in Northeast China for a case study, based on the GHG Protocol and emission factor methodology. The sources of GHG emissions at this university were identified by the GHG Protocol. Activity data were collected through questionnaire surveys and field visits. The results show that the university’s annual carbon footprint in 2022 stands at 172,473.77 t CO2-eq, with the contributions of Scope 1, 2, and 3 accounting for 2.35%, 64.69%, and 32.96%, respectively. Based on the carbon footprint quantification results, campus carbon reduction strategies were put forward from four perspectives: individual activities, building energy management, energy-loss reduction, and carbon sink, in order to enhance the sustainability of this university. An important difference between this work and previous studies is the explicit emphasis on the necessity of the indicative role of the carbon footprint in carbon reduction efforts. The case demonstrates the application of research framework and methods, providing methodologies and case references for future research on the carbon footprint of universities.